Pengaruh Sistem Pengendalian Internal, Whistleblowing System, dan Kesesuaian Kompensasi terhadap Pencegahan Fraud LPD di Kabupaten Tabanan - Dewi, Kadek Ayu Kartika; Anggiriawan, I Putu Budi; Martini, Ni Putu Riski (Jurnal EMT KITA, 2026)
Fraud is a serious problem that can hamper the performance and sustainability of Village Credit Institutions (LPD). The characteristics of LPDs, which have a relatively limited organizational structure and minimal level of external supervision, have the potential to cause information asymmetry and conflicts of interest as explained in agency theory. Based on this framework, this study analyzes the role of the Internal Control System as a formal monitoring mechanism, the Whistleblowing System as an internal detection mechanism, and Compensation Suitability as an incentive alignment mechanism in preventing fraud in LPDs. The study population was all active LPDs in Tabanan Regency. A sample of 150 LPDs was selected using the Slovin formula and then, the sample was divided into each sub-district using a proportional sampling technique. The research data were analyzed using the Structural Equation Modeling approach based on Partial Least Squares (SEM-PLS) to test the relationship between the research variables. The results of the study indicate that the Internal Control System (β = 0.015; p < 0.05), Whistleblowing System (β = 0.845; p < 0.05), and Compensation Suitability (β = 0.170; p < 0.05) have a positive and significant effect on Fraud Prevention. The R² value of 0.989 indicates that the three variables simultaneously explain 98.9% of the variation in Fraud Prevention. This finding emphasizes the importance of strengthening oversight mechanisms and aligning incentives in supporting transparent and sustainable LPD governance.